Back to the basics: Propolis and COVID-19 - Dimitri Bachevski; Katerina Damevska; Viktor Simeonovski; Maja Dimova (Wiley Online Library, 2020)
The epidemiological burden of COVID-19 is a healthcare challenge throughout the world, not only in terms of testing the limits of medical capacities, but also as an enigma considering preventive strategies and methods. The upper respiratory tract mucosa is the first line of defense, as a physical barrier, as well as through multiple innate and adaptive immune mechanisms which are crucial for efficient antiviral responses. Identifying methods able to reduce or prevent colonization, viral adhesion, and promote virus shedding on mucous membranes or have the ability to inactivate pathogens and thus reduce virus dose and/or increase immune response would be essential in the management of COVID-19 outbreak and help in flattening the curve. We review the effects of propolis, an old remedy with proven antiviral properties, as a possible low-cost inhibitor of SARS-CoV-2 in the oropharyngeal niche, prophylaxis, or adjuvant therapy.
Keywords: COVID-19; prevention; propolis; quercetin; SARS-CoV-2